2022
DOI: 10.3390/w14020197
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Soil Organic Carbon and Total Nitrogen in a Ramsar Wetland, Dafeng Milu National Nature Reserve

Abstract: The invasion and expansion of Spartina alterniflora in coastal salt marsh wetlands have greatly affected the material cycle of the ecosystem. A total of 372 topsoil samples were collected from 124 sites representing two land-cover types by implementing an unprecedented high sampling density study in the Dafeng Milu National Nature Reserve. Classical statistics and geostatistics were used to quantify soil organic carbon (SOC) and total nitrogen (TN) spatial distribution. Redundancy analysis (RDA) was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, approximately one-quarter of the spatial variability remains unexplained due to a lack of soil temperature, soil respiration, soil mineral composition, and soil microbial data. Relevant studies have found that under similar external conditions, soil particle size can affect soil nutrients [50]. Soil temperature is an important factor that affects microbial respiration, as well as the absorption and decomposition rate of soil TN.…”
Section: Other Factors Of Soil Tnmentioning
confidence: 99%
“…However, approximately one-quarter of the spatial variability remains unexplained due to a lack of soil temperature, soil respiration, soil mineral composition, and soil microbial data. Relevant studies have found that under similar external conditions, soil particle size can affect soil nutrients [50]. Soil temperature is an important factor that affects microbial respiration, as well as the absorption and decomposition rate of soil TN.…”
Section: Other Factors Of Soil Tnmentioning
confidence: 99%
“…In addition, with increasing depth, the amount of decomposition products of S. alterniflora roots and other withered organs gradually decreased, the organic matter content of the sediment decreased, the sediment structure became denser, and the BD increased. Furthermore, BD is associated with soil texture, and a decrease in clay content and an increase in sand content resulted in a higher BD [38,39].…”
Section: Driving Factors Of Changes In Physicochemical Indexes Of Sed...mentioning
confidence: 99%
“…The change in sediment MC under S. alterniflora vegetation was mainly affected by tidal action. Accumulated water on the sediment surface increases with depth, enhancing soil compaction while diminishing infiltration, resulting in reduced MC [39,40].…”
Section: Driving Factors Of Changes In Physicochemical Indexes Of Sed...mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the expansion of S. alterniflora is a complex process of change, which is affected by many factors. The transformation of the transient spatial pattern of S. alterniflora from vegetation colonization to expansion only took 2-3 years, and soil nutrients may be the main controlling factor (Xie et al, 2019;Yao et al, 2022b). When making the S. alterniflora suitability atlas, the present study comprehensively considered the effects of tidal inundation, soil salinity, artificial ditches, and elkaffected areas on the distribution of S. alterniflora based on previous research results.…”
Section: Uncertainty and Limitations Of S Alterniflora Predictionsmentioning
confidence: 99%